2012
DOI: 10.5923/j.materials.20120201.05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Load and Sliding Velocity on Friction Coefficient of Aluminum Sliding Against Different Pin Materials

Abstract: In the present research, friction coefficients of aluminum sliding against different pin materials are investigated and compared. In order to do so, a pin on disc apparatus is designed and fabricated. Experiments are carried out when different types of pin such as aluminum, copper and brass slide on aluminum disc. Experiments are conducted at normal load 5, 7.5 and 10 N, sliding velocity 0.5, 0.75 and 1 m/s and relative humidity 70%. Variations of friction coefficient with the duration of rubbing at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…However, in our study we have chosen the parameter of normal load. [14] Reported that normal load are ones of major factors whose play significant role for the variation of friction and wear rate. These last ones make their study difficult in laboratory given the difficulty of reproducing the same industrial environment (wear and friction of mechanical parts in some mechanical devices).…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study we have chosen the parameter of normal load. [14] Reported that normal load are ones of major factors whose play significant role for the variation of friction and wear rate. These last ones make their study difficult in laboratory given the difficulty of reproducing the same industrial environment (wear and friction of mechanical parts in some mechanical devices).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental equation (5,6,7) shows that the dynamic friction force F D of the pneumatic cylinder is significantly influenced by the relative humidity and the air temperature. The law of variation of dynamic friction depends on the temperature -humidity as the static friction.…”
Section: Dynamic Frictionmentioning
confidence: 99%
“…The results show that at low RH and high temperature, the wear coefficient is low and vice versa, the wear coefficient is high when the RH is high, and T is low. The studies [3][4][5][6][7][8] have shown that the friction of material pairs is significantly influenced by air humidity, which decreases with increasing relative humidity. The climatic environment characteristics (RH, T) also directly affect the friction of the pneumatic cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…3, d). Увеличение f со временем или расстоянием скольжения объясняется увеличением шероховатости поверхности контакта в процессе трения, которое ранее наблюдалось на алюминии в работе [6]. Второй причиной медленного роста коэффициента трения во всем исследованном интервале температур могло быть повышение температуры вблизи контакта.…”
Section: результаты и их обсуждениеunclassified